1998
DOI: 10.1097/00003226-199803000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Blood-Aqueous Barrier After Corneal Refractive Surgery

Abstract: Using mean results of laser flare meter evaluation, uneventful RK appears to induce short-lasting elevations in aqueous flare in both steroid-treated and untreated patients. Microperforation induced prominent alterations in flare measurements, although limbal bleeding did not. Both PRK and LASIK did appear to increase flare measurements in some eyes, while PTK induced significant elevations in aqueous flare in the majority of eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Our findings in eyes subjected to corneo-limbal cut and perforation (paracentesis) are in agreement with well-established data on paracentesis-induced BAB failure in primates [3,24] and with other experimental models in which inflammation was induced by intraocular injection of leukotriene B4 (LTB4) [37], combined injection of TNF-αand IL-6 [9,13], or TNF alone [10,16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings in eyes subjected to corneo-limbal cut and perforation (paracentesis) are in agreement with well-established data on paracentesis-induced BAB failure in primates [3,24] and with other experimental models in which inflammation was induced by intraocular injection of leukotriene B4 (LTB4) [37], combined injection of TNF-αand IL-6 [9,13], or TNF alone [10,16].…”
Section: Discussionsupporting
confidence: 90%
“…Steroids are known to reduce aqueous protein levels in traumatized eyes: protein levels were diminished by steroids treatment following perforating corneal injury [37], or cataract surgery [27].…”
Section: Discussionmentioning
confidence: 99%
“…The case of recurrent iridocyclitis in our series might have been triggered by PRK, which is known to increase aqueous flare level (23,24). However, subclinical inflammation is a common finding after the implantation of angle-supported phakic IOLs (25), and a 1% incidence of chronic iridocyclitis has been reported after this surgery (26).…”
Section: Discussionmentioning
confidence: 71%
“…It was suggested that the blood ocular barrier is altered following excimer laser procedures and particularly after PRK. For example, increased amounts of flare were measured in the anterior chamber 15 days after PRK [14]. This may facilitate drug penetration into the anterior chamber as well.…”
Section: Discussionmentioning
confidence: 99%